Comunicação intercultural: uma desconstrução e reconstrução de um termo inflacionário. - Schröder, Ulrike (Cadernos de Linguagem e Sociedade, 2010)
Although the term intercultural communication becomes more and more important in scientific discussion originated in distinct areas which are interested in intercultural research, a theoretical and epistemological foundation conceptualizing the term in an appropriate way and considering an analysis of its constitutes rarely can be found. Therefore, first, the term in question is deconstructed by asking for a reasonable understanding of culture and communication. Subsequently, the term will be reconstructed according to the conclusions made, focusing on the question to what extent it might be really possible to talk about a strict delimitation between intracultural and intercultural communication.